2006
DOI: 10.1128/jb.00185-06
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Functional Analysis of the IncP-9 Naphthalene-Catabolic Plasmid NAH7 and Its Transposon Tn 4655 Suggests Catabolic Gene Spread by a Tyrosine Recombinase

Abstract: The naphthalene-catabolic (nah) genes on the incompatibility group P-9 (IncP-9) self-transmissible plasmid NAH7 from Pseudomonas putida G7 are some of the most extensively characterized genetic determinants for bacterial aerobic catabolism of aromatic hydrocarbons. In contrast to the detailed studies of its catabolic cascade and enzymatic functions, the biological characteristics of plasmid NAH7 have remained unclear. Our sequence determination in this study together with the previously deposited sequences rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 67 publications
4
74
0
Order By: Relevance
“…These gene products showed moderate to significant levels of identity with well-studied catabolic enzymes from isolated bacteria; these enzymes included Dmp proteins from the phenolcatabolizing plasmid pVI150 of Pseudomonas sp. CF600 (Shingler et al, 1992), Phe proteins from the phenol-utilizing strain Bacillus thermoglucosidasius A7 (Duffner et al, 2000), Tdn proteins from the aniline-catabolizing plasmid pTDN1 of P. putida UCC22 (Fukumori and Saint, 2001), Nah proteins from the naphthalene-catabolizing plasmid NAH7 of P. putida G7 (Sota et al, 2006a) and Nag proteins from the naphthalene-utilizing strain Ralstonia sp. U2 (Zhou et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These gene products showed moderate to significant levels of identity with well-studied catabolic enzymes from isolated bacteria; these enzymes included Dmp proteins from the phenolcatabolizing plasmid pVI150 of Pseudomonas sp. CF600 (Shingler et al, 1992), Phe proteins from the phenol-utilizing strain Bacillus thermoglucosidasius A7 (Duffner et al, 2000), Tdn proteins from the aniline-catabolizing plasmid pTDN1 of P. putida UCC22 (Fukumori and Saint, 2001), Nah proteins from the naphthalene-catabolizing plasmid NAH7 of P. putida G7 (Sota et al, 2006a) and Nag proteins from the naphthalene-utilizing strain Ralstonia sp. U2 (Zhou et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen genes (ORF1F2-3 to À7 and À16 to À26) in the fosmid were categorized as involved in aromatics degradation (Figures 1 and 4). Of these 16 genes, nine (ORF1F2-7, À16, À17, À20, À21, À23 to À26) encoded products predicted to have 27-53% amino acid sequence identity with those of the enzymes for naphthalene degradation encoded by the nah genes of plasmid NAH7 from P. putida G7 (Sota et al, 2006a) and the nag genes of Ralstonia sp. U2 (Zhou et al, 2001).…”
Section: Aromatic Catabolic Pathways In Microbial Community H Suenagamentioning
confidence: 99%
“…Studies of naphthalene degradation have shown that there are two primary pathways for the metabolism of naphthalene, which are distinguished by the conversion of salicylate to catechol or gentisate. Metabolism of naphthalene via catechol has been studied extensively in two Pseudomonas species that carry the archetypal catabolic plasmids NAH7 (in P. putida G7) and pDTG1 (in P. putida NCIB 9816-4) (Dennis & Zylstra, 2004;Yen & Serdar, 1988;Sota et al, 2006). The nah dissimilatory genes are organized into two operons: one encoding the enzymes involved in the conversion of naphthalene to salicylate (naphthalene degradation upper pathway) and another encoding the conversion of salicylate to catechol, followed by ortho-or meta-cleavage to TCA cycle intermediates (naphthalene degradation lower pathway) (Yen & Gunsalus, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Although the plasmids from Pseudomonas are classified into at least 14 Inc groups, 61) the degradative plasmids characterized to date belong to the IncP-1, -2, -7, and -9 groups. 62,63) Among such four Inc group degradative plasmids, the most detailed analyses have been conducted on the IncP-1 and IncP-9 plasmids: IncP-1, pJP4, [64][65][66] pADP-1, 67,68) and pUO1; 69,70) and IncP-9, pWW0, [71][72][73][74] NAH7, 75,76) pDTG1, 77,78) and SAL1. 79) To date, in addition to pCAR1, complete nucleotide sequences have been reported for three other IncP-7 group plasmids: naphthalene degradative plasmid pND6-1, 80) toluene degradative plasmids pWW53, 81) and pDK1.…”
Section: Replication and Stable Maintenance Machinerymentioning
confidence: 99%